Constructing a database of alien plants in the Himalaya to test patterns structuring diversity - Suresh K. Rana; Bhawana Dangwal; Gopal S. Rawat; Trevor D. Price (Ecology and Evolution, 2024)
Abstract Differences in the number of alien plant species in different locations may reflect climatic and other controls that similarly affect native species and/or propagule pressure accompanied with delayed spread from the point of introduction. We set out to examine these alternatives for Himalayan plants, in a phylogenetic framework. We build a database of alien plant distributions for the Himalaya. Focusing on the well‐documented regions of Jammu & Kashmir (west) and Bhutan (east) we compare alien and native species for (1) richness patterns, (2) degree of phylogenetic clustering, (3) the extent to which species‐poor regions are subsets of species‐rich regions and (4) continental and climatic affinities/source. We document 1470 alien species (at least 600 naturalised), which comprise ~14% of the vascular plants known from the Himalaya. Alien plant species with tropical affinities decline in richness with elevation and species at high elevations form a subset of those at lower elevations, supporting location of introduction as an important driver of alien plant richness patterns. Separately, elevations which are especially rich in native plant species are also rich in alien plant species, suggesting an important role for climate (high productivity) in determining both native and alien richness. We find no support for the proposition that variance in human disturbance or numbers of native species correlate with alien distributions. Results imply an ongoing expansion of alien species from low elevation sources, some of which are highly invasive.